Equações Diofantinas na Educação Básica: Uma Análise à Luz dos Registros de Representação Semiótica - Dalvi, Helder (2021)
The study approaches the theme about the importance of teaching Mathematics in a creative way through the application of Diophantine equations and their resolution in different ways. The general objective of the study is to show TRRS as an efficient strategy for capturing content in solving Diophantine equations in Elementary School. As for the specific objectives, it will be to verify, in the light of the literature, the importance of teacher training and pedagogical practices for the teaching of Mathematics; understand the process that leads to learning improvement through the semiotic register; to present the various forms of transformation of semiotic registers in Diophantine equations; identify the possibilities and difficulties perceived in the classroom in solving Diophantine equations in Mathematics teaching. The research method will be descriptive with a qualitative-quantitative approach and problem solving strategies. The results of this research indicate little exploration regarding the use of Semiotic Representation Records to solve Diophantine equations, however, there was an increase in student performance in the second moment of solving the problems. A range of strategies is recommended to be implemented in order to mitigate the lack of interest on the part of students and, at the same time, encourage the teacher to make use of methodologies that promote interaction, which serve as bridges between them – teachers and students. The study points to the need to create intelligibility of the problems addressed so that criticisms and proposals that cooperate with the elaboration of future/possible actions for the teaching of Mathematics are built.